The Relationship between C-Reactive Protein/Albumin Ratio and Disease Activity in Patients with Inflammatory Bowel Disease - Yi-Han Chen; Li Wang; Shu-Yi Feng; Wei-Min Cai; Xiao-Fu Chen; Zhi-Ming Huang (Gastroenterology Research and Practice)
Objectives. The aims of this study were to evaluate the C-reactive protein/albumin ratio (CRP/ALB), inflammatory markers, and parameters from the complete blood count (CBC) in patients with inflammatory bowel disease (IBD) and their associations with disease activity. Methods. A total of 876 IBD patients, composed of 275 patients with ulcerative colitis (UC) and 601 patients with Crohn’s disease (CD), were included in this retrospective study, and the serum C-reactive protein (CRP), albumin (ALB), erythrocyte sedimentation rate (ESR), and CBC parameters were measured. To explore the disease activity, the Mayo score and Crohn disease activity index were used to assess UC and CD patients, respectively. Results. The CRP/ALB ratio, CRP, ESR, platelet to lymphocyte ratio (PLR), red blood cell distribution width (RDW), and neutrophil to lymphocyte ratio (NLR) levels in active IBD patients were significantly higher than those in inactive IBD patients, whereas ALB and lymphocyte to monocyte ratio (LMR) levels were significantly decreased (P<0.001). The receiver operating characteristic analysis showed that the optimum cut-off values of the CRP/ALB ratio for active UC and CD were 0.18 and 0.43, with sensitivities of 67.8% and 75.8% and specificities of 86.7% and 92.0%, respectively. Multivariable logistic analysis revealed that after adjusting for these inflammatory markers (ESR, NLR, PLR, and LMR), the CRP/ALB ratio was a statistically significant parameter capable of differentiating the disease activity of UC and CD. Conclusions. This study indicated that the CRP/ALB ratio was closely related to the IBD disease activity. Compared with CBC parameters, the CRP/ALB ratio had a higher discriminative capacity for active IBD.